Wave Trajectory Study on the Coast of Lhoknga, Aceh Besar, Indonesia: A Numerical Model Approach - Ichsan Setiawan; Mohammad Irham (Institute of Research and Community Outreach - Petra Christian University, 2018)
A numerical model of wave trajectory using shoaling and refraction formula was proposed in the coastal waters of Lhoknga, Aceh Besar, Indonesia. The developed model used a two dimensional (2D) numerical methods for wave trajectory with the input of wave height and period; 0.62 m and 8 second for high tide and 0.47 m and 6 second for low tide. This model was tested on site during low tide and high tide conditions for verification. The purpose of this numerical study is to trace the distribution of wave trajectory because of shoaling, wave breaking, and wave refraction. The model determines the wave height and crest pattern of the ray wave trajectory. The simulation result shows the pattern of the wave propagation at Lhoknga beach moves from the northwest to the east and south of the coast. The model also informs that the maximum wave height during high tide condition is 1.72 m and 1.31 m during low tide condition. The result indicates that the coast of Lhoknga has moderate wave conditions caused by a gentle beach bathymetry slope.